Obscure Gastrointestinal Bleeding from an Ampullary Tumour in a Patient with a Remote History of Renal Cell Carcinoma: A Diagnostic Conundrum - Rhonda M Janzen; Alnoor S Ramj; Julia DA Flint; Charles H Scudamore; Eric M Yoshida (Canadian Journal of Gastroenterology)
Metastasis of renal cell carcinoma to the ampulla of Vater is a rare occurrence. The outlined case, which presented as an upper gastrointestinal bleed, is only the eighth such reported case in the English-language literature. This case is the longest reported time interval between surgical nephrectomy to presentation with ampullary metastasis at 17.5 years. The ampullary source of bleeding in this case was initially obscure and missed by conventional gastroscopy. Diagnosis was made with a side-viewing endoscope, emphasizing the usefulness of this instrument in the investigation of active bleeding from a small bowel source.